Gastric and colonic metastases of malignant melanoma diagnosed during endoscopic evaluation of symptomatic anemia presenting as angina: a case report - Amaris, Manuel A.; Kallas, Henrique E.; Gonzalo, David H.; Orlando, Frank A. (Frontiers in Medicine, 2023)
A 72-year-old man visited cardiology for exertional chest pain, lightheadedness, and fatigue. Six years prior, he was surgically treated for cutaneous malignant melanoma of the lower back. After a negative cardiac workup, primary care diagnosed a severe iron deficiency anemia. Emergent upper and lower gastrointestinal (GI) endoscopy revealed simultaneous melanoma metastases to the stomach and colon with discrete macroscopic features. Metastatic disease including brain, lung, and bone was discovered on imaging. Treatment included immunotherapy with nivolumab and stereotactic radiosurgery of the brain metastases, and theour patient has remained in continued remission is living a normal life nearly two years later.Melanoma with GI tract (GIT) metastasis has a poor prognosis and rarely presents symptomatically or with synchronous gastric and colonic lesions. This case illustrates the importance of early primary care involvement to expedite work-up for multifocal GI metastases in patients with remote melanoma history presenting with symptoms related to iron deficiency anemia (IDA).